Vertical structure and physical processes of the Madden‐Julian oscillation: Exploring key model physics in climate simulations. Issue 10 (26th May 2015) - Jiang, Xianan; Waliser, Duane E.; Xavier, Prince K.; Petch, Jon; Klingaman, Nicholas P.; Woolnough, Steven J.; Guan, Bin; Bellon, Gilles; Crueger, Traute; DeMott, Charlotte; Hannay, Cecile; Lin, Hai; et al.
Abstract Aimed at reducing deficiencies in representing the Madden‐Julian oscillation (MJO) in general circulation models (GCMs), a global model evaluation project on vertical structure and physical processes of the MJO was coordinated. In this paper, results from the climate simulation component of this project are reported. It is shown that the MJO remains a great challenge in these latest generation GCMs. The systematic eastward propagation of the MJO is only well simulated in about one fourth of the total participating models. The observed vertical westward tilt with altitude of the MJO is well simulated in good MJO models but not in the poor ones. Damped Kelvin wave responses to the east of convection in the lower troposphere could be responsible for the missing MJO preconditioning process in these poor MJO models. Several process‐oriented diagnostics were conducted to discriminate key processes for realistic MJO simulations. While large‐scale rainfall partition and low‐level mean zonal winds over the Indo‐Pacific in a model are not found to be closely associated with its MJO skill, two metrics, including the low‐level relative humidity difference between high‐ and low‐rain events and seasonal mean gross moist stability, exhibit statistically significant correlations with the MJO performance. It is further indicated that increased cloud‐radiative feedback tends to be associated with reduced amplitude of intraseasonal variability, which is incompatible with the radiative instability theory previously proposed for the MJO. Results in this study confirm that inclusion of air‐sea interaction can lead to significant improvement in simulating the MJO.